2022
DOI: 10.1017/gmh.2022.57
|View full text |Cite
|
Sign up to set email alerts
|

Closing the treatment gap for alcohol use disorders in low- and middle-income countries

Abstract: The alcohol-attributable disease burden is greater in low- and middle-income countries (LMICs) as compared to high-income countries. Despite the effectiveness of interventions such as health promotion and education, brief interventions, psychological treatments, family-focused interventions, and biomedical treatments, access to evidence-based care for alcohol use disorders (AUDs) in LMICs is limited. This can be explained by poor access to general health and mental health care, limited availability of relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…This issue is common in many SSA countries, where inadequate budget allocation to alcohol control demonstrates a lack of government commitment [26]. Similarly, key services for the treatment and rehabilitation of alcohol use disorders are often absent in SSA [27][28][29],…”
Section: Implementing Agency Responsementioning
confidence: 99%
“…This issue is common in many SSA countries, where inadequate budget allocation to alcohol control demonstrates a lack of government commitment [26]. Similarly, key services for the treatment and rehabilitation of alcohol use disorders are often absent in SSA [27][28][29],…”
Section: Implementing Agency Responsementioning
confidence: 99%
“…Literature on AUDs demonstrates an increased risk for mental health disorders (Grant et al, 2004 ; Lo et al, 2017a ), noncommunicable diseases (Hammer et al, 2018 ; Nadkarni et al, 2023a ), gender-based violence (Shiva et al, 2021 ) and wider social and economic risks (Hammer et al, 2018 ). People with AUDs often experience barriers to treatment which can reduce health seeking behavior and underutilization of services (Probst et al, 2015 ; Mellinger et al, 2018 ; McCrady et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that attitudinal barriers were more critical in high-income settings and structural barriers were more likely in LMICs (Sareen et al, 2007 ; Roberts et al, 2018 ). However, available evidence suggested that both attitudinal and structural barriers are important in hindering or delaying treatment in low-resource settings (Andrade et al, 2014 ; Nadkarni et al, 2023 ). For example, a previous Ethiopian study reported that major barriers to seeking treatment for alcohol use disorder included low perceived need and a lack of knowledge about where to seek help (Zewdu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%